CONTROLE ESTRATÉGICO DE Rhipicephalus microplus EM DUAS ESTAÇÕES - Guilherme Henrique Reckziegel (2022)
RECKZIEGEL, G. H. Strategic control of Rhipicephalus microplus in two seasons. 2022. MESTRADO – Programa de Pós-Graduação em Ciências Veterinárias. Faculdade de Medicina Veterinária e Zootecnia, Universidade Federal de Mato Grosso do Sul, Campo Grande, MS, 2022. The strategic control protocols for Rhipicephalus microplus on cattle recommended for the semi-humid Brazilian cerrado region consists of treatments at the beginning of the rainy season, considering the occurrence of four peaks of tick infestation throughout the year. However, in some circumstances, such as the occurrence of winters with higher temperatures, a fifth peak is possible in the winter months. For this reason, a strategic control protocol was developed with treatments in two seasons, to also control the generations that occur in spring/summer, such as autumn/winter. The study was carried out in Ribas do Rio Pardo, MS, from the beginning of the rainy season in 2020 (November) until October 2021. 36 Nellore x Angus heifers were distributed using a randomized block design, based on weight and average ticks at dzero, into three groups: i) Negative control; ii) One-season strategic control (beginning of the rainy season); and iii) Two-season strategic control (beginning and end of the rainy season). The two strategic control groups were treated on D0 (October/2020), and twice more every 42 days. The two-season strategic control group received three additional treatments every 42 days from D182 (May/2021) . All treatments were performed with 5% fluralaner via pour-on at a dosage of 1mL/20kg BW. Each group was kept in exclusive paddocks. Semi-engorged female tick counts (4.5 to 8 mm) were performed on the left side of the animals on D3 and every 14 days, when the animals were also weighted. Fluralaner showed efficacy above 95% until D294, with the exception of D40 (94.2%), when there was a sudden reduction in the average number of ticks in control group. The two treated groups showed a decrease (p<0.05) in the mean number of ticks from the third day after the first treatment. In the two-season strategic control group, the means were close to or equal to zero throughout the study, while in the one-station group the means did not differ (p>0.05) from the control group from D231 onwards. The final average weight gain of each group was 115.38kg, 98.63kg and 76.40kg for the two-season, one-season and control groups, respectively, differing (p<0.05) from each other. Therefore, three applications starting 42 days from the start of the rainy season resulted in effective control for 222 days, and, when performed three more treatments every 42 days in autumn/winter, tick counts were reduced throughout the year. Thus, in years with climatic conditions being predicted period of occurrence of peaks in autumn/winter, a second treatment is recommended in this period. Keywords: Brazilian cerrado; cattle breeding; cattle tick; seasonality.